2022
DOI: 10.21468/scipostphysproc.7.022
|View full text |Cite
|
Sign up to set email alerts
|

The pion-photon transition form factor at two loops in QCD

Abstract: We report on the fully analytic calculation of the leading-power contribution to the photon-pion transition form factor \gamma \, \gamma^{\ast} \to \pi^0γγ*→π0 at two loops in QCD. The applied techniques are based on hard-collinear factorization, together with modern multi-loop methods. We focus both, on the technical details such as the treatment of evanescent operators, and the phenomenological implications. Our results indicate that the two-loop correction is numerically comparable to the one-loop effect in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…In fact it can be found that for the result in [12,13] we get f = f , h = h up to two-loops (and possibly to higher orders). Hence the same formulas as in eq.…”
Section: One-loop Calculation and Nll Resummationmentioning
confidence: 95%
See 1 more Smart Citation
“…In fact it can be found that for the result in [12,13] we get f = f , h = h up to two-loops (and possibly to higher orders). Hence the same formulas as in eq.…”
Section: One-loop Calculation and Nll Resummationmentioning
confidence: 95%
“…It is well-known that there is ambiguity in defining γ 5 in dimensional regularization. In the two-loop calculation of C q [12,13] Larins scheme [14] was used and the result is then converted by a finite renormalization to the conventional MS-scheme, which is defined by demanding that the evolution equation agrees with the vector case [15]. Larins scheme can be implemented by making the exchange…”
Section: One-loop Calculation and Nll Resummationmentioning
confidence: 99%